RANCANG BANGUN APLIKASI CERDAS (LIMBEKFEED) MENGGUNAKAN METODE PROFILE MATCHING DALAM PENENTUAN DOSIS PEMBERIAN PAKAN TERNAK IKAN LELE - Ridho, Abdurrahman; Putri, Andriani (Universitas Islam Balitar, 2023)
In catfish farming, providing the right feed is crucial for optimal growth and health. However, determining the accurate dosage of feed that is suitable for individual catfish can be complex and time-consuming. To address this challenge, we have developed an intelligent application called